Scanning Electrochemical Microscopy Studies of Redox Processes at Undoped Nanodiamond Surfaces - Holt, K; Ziegler, C; Zang, J; Hu, J; Foord, J (2009)
The redox behavior of an undoped nanodiamond (ND) film grown by chemical vapor deposition was investigated using cyclic voltammetry (CV) and scanning electrochemical microscopy (SECM) and redox mediators Fe(CN)63-, Fe(CN)64-, ferrocenemethanol (FcOH), and Ru(NH3)63+. CV showed extremely sluggish kinetics for all redox couples, but the reduction of Fe(CN)63- was found to be especially slow when compared to the oxidation of Fe(CN)64-. SECM confirmed this trend, with experimental heterogeneous rate constants, obtained by fitting approach curves to theory, being of the magnitude of 10-3 cm s-1. The oxidation of Fe(CN)64- at an overpotential, |η|, of 0.6 V was found to occur 5 times faster than the reduction of Fe(CN)63- at the same |η|. The results are explained by assuming conduction takes place through extended sp2 (graphitic and defect sites) through the film. The nondiamond component of the film introduces impurity bands into the band gap that allows limited metallic type conductivity. The slow electron transfer was attributed to the very small percentage of the surface that was electrochemically active and hence relatively narrow impurity bands and limited carrier numbers. About 2% of the surface was calculated to be active in the potential range -0.4 to 0.5 V vs Ag/AgCl. At >0.5 V, the active area was found to increase with applied potential up to about 10% at 0.8 V. This increase in active electrode area explains the faster rate constants obtained for the oxidation of Fe(CN)64- at these potentials. It is postulated that the increase in active area is due to oxidation of defect sites of the film to form electron deficient, hence redox active, centers. This results in the widening of the impurity bands in the band gap and hence an increased density of states. Approach curves to a layer of 5 nm ND powder using the same redox couples exhibited a similar trend, with reduction of Fe(CN) 63- taking place much slower than oxidation of Fe(CN) 64-. Overall, rate constants were about 10 times faster at the powder interface than the film. It is believed that electron transfer at the ND nanoparticle surface takes place at similar sites as on the ND film but that they are present at higher relative concentrations due to the higher surface to bulk atom ratio of the nanoparticles. © 2009 American Chemical Society.